The violence in the daily school routine - Leila Maria Ferreira Salles; Joyce Mary Adam de Paula e Silva; Juan Carlos Revilla Castro; Concepción Fernandez Villanueva; Roberto Domínguez Bilbao (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
The present paper presents a reflection on the processes of interaction that take place inside the school. They are associated to situations of prejudice and stigma and they trigger conflicts and violence. The daily routine at schools is marked by violence such as segregation, exclusion and indifference to the other. It is important to analyze the practices transmitted in the school environment looking for the unveiling and not the covering of discrimination and intolerance that may generate violence among teenagers and youngsters in the school context and between students and educators.